Malnutrition identification according to mini nutritional assessment- short Form and dietary intake among community living elderly in Kuantan, Pahang - Hamirudin, Aliza Haslinda; Muhamad, Abdul Rahman; Mohammad Rosli, Nur Izzati (Nutrition Society of Malaysia, 2017)
Malnutrition is under recognized and remains a problem in elderly population. However, study related to malnutrition among community living elderly population in Malaysia specifically in Kuantan is scarce. Thus, this study aimed to identify prevalence of malnutrition in elderly population in Kuantan while determining associated factors, and to assess energy and protein intake of the elderly. Seventy-three community living elderly (n= 39 men and n= 34 women) aged 60 years and older were recruited from Kuantan, Pahang. Malnutrition was assessed by using a validated nutritional screening tool for elderly, the Mini Nutritional Assessment- Short Form (MNA-SF). Diet history was used to collect dietary intake data and was analysed with the use of Nutritionist Pro Software. All data were statistically analyzed by using SPSS software version 12.0. Statistically significant level was set at p<0.05. 47 participants (64.4%) were identified in malnutrition and at risk of malnutrition categories (score= 0-11), whilst 26 participants (35.6%) were well nourished (score= 12-14). Only two factors showed significant association with malnutrition risk; income per month (p = 0.045) and frequency of physical activity (p= 0.039). Mean energy (1287.50 ± 404.11 kcal/day) and protein (47.40 ±14.28 gram) intake of the elderly were lower than recommended intake. In conclusion, timely malnutrition identification and nutrition intervention should be taken to prevent health deterioration and improve quality of life.